2011
DOI: 10.1136/bjophthalmol-2011-300655
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of subretinal coapplication of rtPA and bevacizumab followed by repeated intravitreal anti-VEGF injections for neovascular AMD with submacular haemorrhage

Abstract: The operation effectively displaces small and large SMHs. In the long-term, a predominantly visual acuity-driven re-treatment regimen puts the initial functional improvement at risk. More sensitive re-treatment parameters may help to improve long-term functional outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
77
0
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 22 publications
6
77
0
6
Order By: Relevance
“…9,10 A recent review by Stanescu-Segall et al 20 summarises the findings of these previous studies. To date, there is no consensus on the optimal management for patients presenting with this severe complication of nAMD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…9,10 A recent review by Stanescu-Segall et al 20 summarises the findings of these previous studies. To date, there is no consensus on the optimal management for patients presenting with this severe complication of nAMD.…”
Section: Discussionmentioning
confidence: 99%
“…10 Random effect meta-analysis showed that the incidence of RPE rips, macular hole, and retinal detachments is ∼ 2.3% (95 CI 0-5.5%) for each of these complications in this procedure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, in the Submacular Surgery Trial (SST), 440% of eyes exhibited lesion sizes larger than 16 DAs, and improvement in visual acuity by three lines or greater during 6 months was only achieved in 10% of eyes in the observation group and 11% of eyes in the surgery group. 10 In another investigation of patients with relatively small SMH areas, Treumer et al 16 reported that 12 of 26 eyes (46.1%; mean baseline hemorrhage area = 4.5 DA; mean follow-up time = 17 months) had BCVA improvements of ≥ 3 lines Figure 1 Changes in mean best-corrected visual acuity (BCVA) and mean central foveal thickness in eyes with large submacular hemorrhage (SMH) secondary to neovascular age-related macular degeneration (nAMD) after treatment. The mean BCVA showed significant improvements during the follow-up period (a), and the mean central foveal thickness (b) also showed significant improvements during the follow-up period (*Po0.05).…”
Section: Discussionmentioning
confidence: 99%